Dietary change and food demand in urbanizing Bangladesh - Ecker, Olivier; Comstock, Andrew R. (International Food Policy Research Institute, 2021)
Poor-quality diets are one of the leading causes of malnutrition and common non-communicable disease. In this study, we use nationally representative household survey data and food demand system estimations to analyze dietary change and changing consumer preferences for different foods in the context of urbanization in low- and middle-income countries. We estimate and compare income and price elasticities of total food demand and the demand for 15 food groups in rural, urban, and city areas of Bangladesh for 2010 and 2016. We then use Oaxaca-Blinder decomposition regressions to explore how much of the observed food consumption changes can be explained by changes in revealed consumer preferences vis-à-vis changes in household income and food prices. The results show that Bangladeshi diets shifted from coarse to refined rice, and consumer preferences for vegetables and pulses were relatively low, contributing to worsening dietary quality. On the other hand, the consumption of nutritious, animal-source foods including fish, poultry, and eggs increased due to high consumer preferences and declining food prices-partly thanks to governmental production support. Regarding the dietary implications of rapid urbanization, the analysis suggests that rural consumers’ diets will largely follow the trajectory of urban consumers in Bangladesh.